A Hybrid Electrolytes Design for Capacity‐Equivalent Dual‐Graphite Battery with Superior Long‐Term Cycle Life. Issue 24 (1st July 2018) - Qiao, Yu; Jiang, Kezhu; Li, Xiang; Deng, Han; He, Yibo; Chang, Zhi; Wu, Shichao; Guo, Shaohua; Zhou, Haoshen
Abstract: Based on cation/anion graphite intercalation chemistry (GIC) processes, dual‐graphite batteries promise to be an energy storage device of high safety and low cost. However, few single electrolyte systems can simultaneously meet the requirements of both high oxidative stability during high voltage anion‐GIC on cathode and high reversibility upon cation‐GIC on anode. Thus, in order to rigidly remedy the irreversible capacity loss, excessive electrode materials need to be fabricated within full cell, resulting in an imbalance toward capacity‐dependent mass loading proportion between both electrodes. This work introduces a hybrid (dual‐organic) electrolytes design strategy into this promising technology. Segregated by a Nafion‐based separator, an ionic liquid electrolyte within the cathodic side can endure high operation potentials, while high Li‐GIC reversibility can be achieved in a superconcentrated ether‐based electrolyte on the anode side. On a mechanistic level, various cation‐GIC processes conducted in different electrolyte systems are clearly revealed and are summarized based on systematical characterizations. More importantly, after synergistically tuning the advantage and drawback of each electrolyte in this hybrid system, the dual‐graphite full cell assembled with capacity‐equivalent graphite‐based electrodes (1:1 mass loading) demonstrates superior long‐term cycling stability with ultrahigh capacity retention for over 3000 cycles. Abstract : A novel organic/organic‐combined hybrid electrolytes design strategy has been introduced into dual‐graphite batteries. The advantages of both electrolytes can be sufficiently utilized (strong oxidative stability of ionic liquid and good Li‐graphite intercalation chemistry reversibility of superconcentrated ether electrolyte). Simultaneously, each of their drawbacks can be well restrained by spatially isolated away from corresponding electrodes.